Pengembangan Program Akselerasi : (Pemikiran Pengembangan Pendidikan Islam) - Afiful Ikhwan (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2015)
Accelerated learning program (acceleration) is a program of special education services for students who have the ability and extraordinary intelligence to learn faster completion time or earlier than the time specified, at every level of education. But what about the learners' psychological review? How aspects and review of educational experts? accurate to the program applied to education in Indonesia? all will be discussed in this paper.